The dynamic digital disk. - Bell, A.E.
The DVD (digital versatile disk) standard was the first format to truly unite the computer and consumer electronics environments-but it also launched an unprecedented debate about copy protection. The DVD is much more than just a new and improved version of the CD. Advances in optical storage, signal processing, and disc manufacturing technology have emerged in the 15 years or so since the CD's birth, and the new disc includes or builds on many of them. But DVD has also been a wake-up call for the motion picture and music industries, rousing them to ready their intellectual property for the new age of digital distribution of content. Four main specifications apply to the physical media itself: one each for the DVD-ROM, DVD-RAM, DVD-R, and DVD-RW. Next, at the logical layer, a common file system specification supports all applications. Named the Universal Disc Format (UDF), it was developed by the Optical Storage Trade Association, Santa Barbara, Calif. Together, the logical and physical layers support an overlying set of applications defined by the DVD-Video, DVD-Audio, and (as yet developmental) DVD-Professional specifications
Keywords: CD; DVD-Audio specification; DVD-Professional specification; DVD-R.; DVD-RAM.; DVD-ROM.; DVD-RW.; DVD-Video specification; Optical Storage Trade Association; Santa Barbara; Universal Disc Format; Common file system specification; Computer environment; Consumer electronics; Copy protection; Digital content distribution; Digital versatile disk standard; Disc manufacturing technology; Dynamic digital disk; Intellectual property; Logical layer; Motion picture industry; Music industry; Optical storage; Physical layers; Signal processing